Reaction of naphthoquinones with substituted nitromethanes. Facile synthesis and antifungal activity of naphtho[2,3- d]isoxazole-4,9-diones - Santos, Maria M. M. (2011)
We report here a simple entry into naphtho[2,3-d]isoxazole-4,9-dione system containing a EWG in position 3 using the readily available 2,3-dichloro-1,4-naphthoquinone and nitromethyl derivatives in the presence of base. Antifungal activity of synthesised naphthoquinones was evaluated against ATCC and PYCC reference strains of Candida. The results suggest that the naphtho[2,3-d]isoxazole-4,9-dione scaffold has the potential to be developed into novel and safe therapeutic antifungal agents.